The Means to an End: Phonology’s Prominence in a Reading Task - Grabovac, Anna (Lingua Frankly, 2017)
For decades, psycholinguists have engaged in a debate over the steps involved in the reading process. Do readers find meaning in texts through a phonological route or a lexical route? This paper, which takes into account two previous studies, investigates the influence of phonology and lexical spelling by analyzing the results of a reading judgment task.